Association between Anemia in Pregnancy and Preterm Birth at Sunpasitthiprasong Hospital - Suthinee Saluckpetch; Pongsun Puntachai (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To determine the association between anemia in pregnancy and preterm birth, maternal and neonatal complications.Materials and Methods: A retrospective cohort study was conducted in pregnant women having a hemoglobin level at their first antenatal care and who delivered at Sunpasitthiprasong Hospital from January 2015 to December 2016. A total of 300 medical records of pregnant women were randomized from the database, of which 150 women were anemia (hemoglobin < 11 g/dL) and 150 women who were non-anemia (hemoglobin ≥ 11 g/dL). Maternal characteristics, gestation age of delivery, route of delivery, maternal and neonatal complications were recorded.Results: Preterm birth in the anemic group (n = 11, 7.3%) was higher than those in non-anemic group (n = 7, 4.7%) but there were no significant differences (p = 0.332). Maternal complications showed no significant differences between the groups (postpartum hemorrhage p = 0.442 and pregnancy induce hypertension p = 0.759). With respect to neonatal complications, there were no significant differences between the groups (low birth weight p = 0.821, birth asphyxia at 1 minute p = 0.315, neonatal unit admission p = 0.143 and respiratory distress syndrome p = 0.570). There were no birth asphyxia at 5 minutes, necrotizing enterocolitis and intraventricular hemorrhage in the relevant groups.Conclusion: There was no significant difference of preterm births between the anemic group and the non-anemic group. Regarding the maternal and neonatal complications, there were no significant differences between the groups.